The current status of radiotherapy in the definitive treatment of lung cancer in a developing country: Turkey - Yalman, Deniz; Köylü, Murat; Sert, Fatma; Çağlar, Hale Başak (Elsevier Science, 2017)
Background: To investigate the current status of radiotherapy (RT) trends in the definitive treatment of lung cancer in Turkey. Methods: A questionnaire consisting of 46 questions about the technical facilities, and indications regarding the definitive radiotherapy of lung cancer was sent to 62 centers in Turkey, and was answered by 47 centers.
WOS: 000413055802261
Keywords: Lung Cancer; Definitive Radiotherapy; Developing Country